Unconventional Rose Odorants: Serendipitous Discovery and Unique Olfactory Properties of 2,2-Bis(prenyl)-3-oxobutyronitrile and Its Derivatives - Hauser, Nicole; Kraft, Philip; Carreira, Erick M. (Synthesis, 2018)
2,2-Bis(3-methylbut-2-enyl)-3-oxobutanenitrile [2,2-bis(prenyl)-3-oxobutyronitrile], an unusual bifunctional nitrile odorant with a fruity rosy, green odor was found to exhibit surprising differences in its detection thresholds (0.25 ng/L air for hyperosmics; 19 ng/L air for hyposmics) and perceived odor characters. To investigate this remarkable phenomenon, 13 derivatives of 2,2-bis(3-methylbut-2-enyl)-3-oxobutanenitrile were synthesized by either monoalkylation of 3-oxo-2-phenylbutanenitrile, or by dialkylation of sodium 1-cyano-2-oxopropan-1-ide or methyl or ethyl cyanoacetate, or by direct derivatization of 2,2-bis(3-methylbut-2-enyl)-3-oxobutanenitrile via its vinyl triflate and Negishi cross coupling. These systematic permutations of the substitution pattern allowed some insight to be gained into the underlying structure–odor relationships and the construction of a simple olfactophore model, albeit no final conclusion could be drawn as to whether the nitrile or carbonyl function acts as the prime osmophore of the bifunctional compounds. Depending on slight genetic variations and the corresponding differences in the receptor morphology both can engage in H-bond interactions with the olfactory receptors, which might explain the observed largely diverging sensitivities. Methyl 2-cyano-2,2-bis(3-methylbut-2-enyl)acetate with a uniform odor threshold of 0.38 ng/L air turned out to be the most interesting floral, rosy odorant of this study, followed by 3-methyl-2,2-bis(3-methylbut-2-enyl)but-3-enenitrile with only a nitrile function and varying odor thresholds (0.40 ng/L air vs. 125 ng/L air).
Keywords: bifunctional compounds; cross coupling; dialkylation; fragrance materials; molecular modeling; nitriles; rose odorants; structure–odor correlation